Algorithms development for financial problems - Vasudevan Prabhakaran (2009)
A challenging task, spanning across various industries in the modern world, is to solve complex practical problems classified as NP-hard. NP-hard stands for Non deterministic Polynomial-time hard. It represents a class of problems that are computationally intractable, implying that it is overwhelming to solve these problems within a traceable time period. The real challenge to solve such NP-Hard problems is in the algorithm front, to develop efficient algorithms that can be implemented within a limited time frame.